Two-stage and sequential unbiased estimation of N in binomial trials, when the probability of success p is unknown. Issue 3 (30th September 2022) - Malinovsky, Yaakov; Zacks, Shelemyahu
Abstract: We propose two-stage and sequential procedures to estimate the unknown parameter N of a binomial distribution with unknown parameter p, when we reinforce data with an independent sample of a negative binomial experiment having the same p .